2006
DOI: 10.1108/07363760610712966
|View full text |Cite
|
Sign up to set email alerts
|

A strategic approach to building online customer loyalty: integrating customer profitability tiers

Abstract: Purpose-The purpose of this paper is to present a strategic framework to managing online loyalty. Design/methodology/approach-The paper integrates concepts including a range of recently published (1993-2006) theoretical works in consumer loyalty and ongoing case developments in internet practice. Findings-Provides information and action approaches to consumer marketers that may increase the success providing want satisfying market offerings. Outlines the costs and benefits of some online customer loyalty build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 14 publications
6
75
0
3
Order By: Relevance
“…In fact, customer descriptions were very utilitarian and transaction based. This finding is in line with previous research that found the concept of customer loyalty not something that consumers recognize, and, when distilled to its simplest definition, loyalty might be viewed as simply whether or not the customer will make a repeat purchase (Pitta, Franzak, & Fowler, 2006). However for franchisees and company management, the concept of loyalty included the likelihood of repeat purchasing, for instance, "To keep my customers where they belong in my database and not going anywhere else," as one franchisee expressed.…”
Section: Good Relationships Lead To Loyaltysupporting
confidence: 81%
See 1 more Smart Citation
“…In fact, customer descriptions were very utilitarian and transaction based. This finding is in line with previous research that found the concept of customer loyalty not something that consumers recognize, and, when distilled to its simplest definition, loyalty might be viewed as simply whether or not the customer will make a repeat purchase (Pitta, Franzak, & Fowler, 2006). However for franchisees and company management, the concept of loyalty included the likelihood of repeat purchasing, for instance, "To keep my customers where they belong in my database and not going anywhere else," as one franchisee expressed.…”
Section: Good Relationships Lead To Loyaltysupporting
confidence: 81%
“…Research has shown that integrating personal contact with select customers can be valuable and increase company profits (Pitta et al, 2006). This type of integration can strengthen a firm's offering and is supported by previous studies purporting that eCRM is much broader than simply a technology (Q.…”
Section: Balancing Human and Computer Interactionsupporting
confidence: 48%
“…E-tailers have more disadvantages when interacting with customers than when transacting off -line. Various disadvantages of transacting online have been recognized by many researchers as the factor diff erentiating off -line services from online ones, especially for products/services requiring more detailed information (Pitta, Franzak & Fowler, 2006;Yoo et al, 2010). Despite the identifi cation by previous studies of the disadvantages of online transactions, these studies have not fully captured the idea as to how e-commerce can resemble off -line transactions.…”
Section: Introductionmentioning
confidence: 78%
“…Customer intimacy is defined as "making customers feel good whenever they make contact with your company" (Ballou, 2006, p. 5, cited in IBM Global Services, 2006 or, alternatively, "tailoring and shaping products and services to fit the increasingly specific definition of the customer" (Bügel, 2010, p. 65). Previous empirical work has shown that the interaction between the service employee and the customer is the most important determinant of customer intimacy (Fleming et al, 2005;Lloyd & Luk, 2011;Pitta et al, 2006). In the academic literature on student loyalty, researchers like Annamdevula and Bellamkonda (2016) have studied the mediating role of student satisfaction on service quality and loyalty.…”
Section: Extant Model 3: Intimacy Will Indirectly Mediate the Relatiomentioning
confidence: 99%
“…As cited in de Waal et al (2016), customer intimacy is defined as "making customers feel good whenever they make contact with your company" (Ballou, 2006, p. 5, cited in IBM Global Services, 2006 or "tailoring and shaping products and services to fit the increasingly specific definition of the customer" (Bügel, 2010, p. 65). Empirically, past researchers ( for more details see, Fleming et al, 2005;Lloyd & Luk, 2011;Pitta et al, 2006, Lau, 2000Xu & Van der Heijden, 2005;Yim et al, 2008) observed that having a good interaction with customers and employees of an organisation impact on customer intimacy. Typically, Yim et al (2008) study suggest that good customer service from an employee leads customers to have intimacy with the organization which leads to customer loyalty.…”
Section: Introductionmentioning
confidence: 99%